THE QUALITY OF DOCTORAL STUDIES: CHALLENGES AND FUTURE PERSPECTIVES - Palkova, Karina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The doctorate studies are one of the highest degrees given by a university. Doctoral studies provide students with training in research techniques. The doctoral studies involves the presentation and preparation of the most value activity named as doctoral thesis. There are a lot of doctoral programmes whose specific objectives are to train researchers to successfully address the challenges of new researched science ECT. Nevertheless the global tendency shows that doctoral studies must be transformed to promote innovative and comprehensive research degree and the particular system of the doctoral study process. The aim of the study is to research the key issues of the quality of doctoral studies from the perspective of innovation and digitalization era in educational system in Europe as a whole and in Latvia.